The impact of technology to silk cocoon producers - Gesite, Charity Contado; Elumba, Patricia Santos (2002.)
The three government agencies concerned with the textile sector and engaged in the development of the Philippine silk industry are the Philippine Textile Research Institute (PTRI), the Fiber Industry Development Authority (FIDA), and the Sericulture Research and Development Institute (SRDI). Among these agencies, the SRDI serves as the national center for sericulture. It is commissioned to develop sericulture as an agro-ecological zones in the country. It has sericulture projects of which six of them are the subjects of the study. It includes Sta. Monica and Cacapian Sericultural Projects in La Union; Sto. Domingo, Magsingal, Nagtupacan and Nalvo Sericultural Projects in Ilocos Sur. This study identifies and describes the cocoon production output of these six SRDI-assisted sericulture projects to assess the viability of the industry. Results of the study show that the silk cocoon producers have met the Institute's expectation. This is attributed to the compliance of the farmers to the technology in mulberry cultivation and silkworm rearing. Although not fully observed, their cocoon yield has provided the farmers satisfactory income that drives them to expand their venture. Further assistance to the farmers is found necessary in mulberry field maintenance and rearing of silkworms for a more efficient and productive industry.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Silk industry -- Philippines